Adverse Childhood Experiences and Amygdalar Reduction: High-Resolution Segmentation Reveals Associations With Subnuclei and Psychiatric Outcomes. (November 2019) - Oshri, Assaf; Gray, Joshua C.; Owens, Max M.; Liu, Sihong; Duprey, Erinn Bernstein; Sweet, Lawrence H.; MacKillop, James
The aim of the present study was 2-fold: (1) to utilize improved amygdala segmentation and exploratory factor analysis to characterize the latent volumetric structure among amygdala nuclei and (2) to assess the effect of adverse childhood experiences (ACEs) on amygdalar morphometry and current psychiatric symptoms. To investigate these aims, structural (T1) MRI and self-report data were obtained from 119 emerging adults. Regression analysis showed that higher ACE scores were related to reduced volume of the right, but not the left, amygdalar segments. Further, exploratory factor analysis yielded a two-factor structure, basolateral and central-medial nuclei of the right amygdala. Stractual equation modeling analyses revealed that higher ACE scores were significantly related to a reduced volume of the right basolateral and central-medial segments. Furthermore, reduction in the right basolateral amygdala was associated with increased anxiety, depressive symptoms, and alcohol use. This association supports an indirect effect between early adversity and psychiatric problems via reduced right basolateral amygdalar volume. The high-resolution segmentation results reveal a latent structure among amygdalar nuclei, which is consistent with prior work conducted in nonhuman mammals. These findings extend previous reports linking early adversity, right amygdala volume, and psychopathology.